KCl-induced repetitive cortical spreading depression inhibiting trigeminal neuronal firing is mediated by 5-HT1B/1D and opioid receptors. (November 2022) - Supronsinchai, Weera; Hoffmann, Jan; Akerman, Simon; Goadsby, Peter J
Background: We aimed to examine the effects of repetitive cortical spreading depression on the responses of nociceptive trigeminal neurons with dural afferents and characterize the role of 5-HT1B/1D and opioid receptors. Methods: Trigeminocervical complex neurons ( n  = 53) responsive to nociceptive activation of the dura mater were studied in rats using electrophysiological techniques. Results: A sub-population ( n  = 32) showed an average inhibition of dural-evoked responses of 65 ± 14% from baseline with cortical spreading depression. This response was reversed by the selective 5-HT1B/1D receptor antagonist, GR127935 (3 mg/kg; n  = 6, iv), and a non-selective opioid receptor antagonist, naloxone (1.5 mg/kg; n  = 6, iv), five minutes after injection. To determine the role of the nucleus raphe magnus in the trigeminocervical complex inhibitory effect, microinjection of lidocaine (2%, n  = 6) or muscimol (100 mM, n  = 5) into the nucleus raphe magnus was performed. There was no effect on cortical spreading depression-induced inhibition of neuronal firing in trigeminocervical complex by either. Conclusion: The data demonstrate that repetitive cortical spreading depression inhibits a subpopulation of dural nociceptive trigeminocervical neurons, an effect mediated by serotonin and opioid receptors. This inhibition does not involve modulation of nucleus raphe magnus neurons.